Diversity, equity, accessibility, and inclusion in museums - Cole, Johnnetta B.; Lott, Laura L. (American Alliance of Museums, 2019)
"In this edited volume, thought leaders in the museum field contemplate the field's struggles with diversity, equity, accessibility, and inclusion. For the first time, these watershed essays, keynote addresses, and data are gathered in one resource, so we can learn from recent history and build on these leaders' work in the next decade."--Provided by publisher.